2005
DOI: 10.1021/la051837g
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Study of Early Morphological Changes during Apoptosis

Abstract: Apoptosis is defined by a distinct set of morphological changes observed during cell death including loss of focal adhesions, the formation of cell membrane buds or blebs, and a decrease in total cell volume. Recent studies suggest that these dramatic morphological changes, particularly apoptotic volume decrease (AVD), are an early prerequisite to apoptosis and precede key biochemical time-points. Here we use atomic force microscopy to observe early stage AVD of KB cells undergoing staurosporine-induced apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 29 publications
6
68
1
1
Order By: Relevance
“…Recently, in a study of early morphological changes during staurosporine-induced apoptosis using atomic force microscopy in human epidermoid carcinoma (KB) cells, AVD was shown to precede key biochemical hallmarks of apoptosis including loss of the mitochondrial membrane potential, externalization of membrane phosphatidylserine, nuclear fragmentation, and measurable caspase-3 activity [26]. Additionally, it has been shown that AVD once initiated occurs within 12 to 20 minutes depending on the cell type and stimulus studied [27;Bortner and Cidlowski,unpublished data].…”
Section: Potassium As a Key Player In The Regulation Of Apoptosismentioning
confidence: 99%
“…Recently, in a study of early morphological changes during staurosporine-induced apoptosis using atomic force microscopy in human epidermoid carcinoma (KB) cells, AVD was shown to precede key biochemical hallmarks of apoptosis including loss of the mitochondrial membrane potential, externalization of membrane phosphatidylserine, nuclear fragmentation, and measurable caspase-3 activity [26]. Additionally, it has been shown that AVD once initiated occurs within 12 to 20 minutes depending on the cell type and stimulus studied [27;Bortner and Cidlowski,unpublished data].…”
Section: Potassium As a Key Player In The Regulation Of Apoptosismentioning
confidence: 99%
“…[18][19][20][21] Previous study indicated that the cell morphology 22,23 and the cytoskeletal filaments 24 would affect the mechanical properties. To gain a comprehensive picture of the structures of hAFSCs and differentiated osteoblasts, AFM was utilized to obtain high-resolution three-dimensional morphology (Fig.…”
Section: Afm Image Of the Hafscs And Differentiated Osteoblastsmentioning
confidence: 99%
“…The decreased fluorescence intensity of FMSNs after 24 h incubation may be due to the apoptosis-induced increase in cell membrane permeability and the accelerated nanoparticle diffusion. 36 Furthermore, MTT tests were conducted to elucidate the therapeutic potential of the nanovehicles. A cancer cell growth inhibitor effect was observed in HeLa cells and NIH-3T3 cells after treatment with FHMSNs@GNC@HA, Dox-FHMSNs-Pep1, Dox-FHMSNs@GNC or Dox-FHMSNs@GNC@HA.…”
Section: Controlled Drug Release Within the Cells And Selective Toxicitymentioning
confidence: 99%